2023
DOI: 10.1590/1519-6984.244479
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis, in vitro cytotoxicity and antibacterial studies of bioactive principles from the leaves of Conocarpus lancifolius, a common tree of Jazan, Saudi Arabia

Abstract: The objective of the present study was to analyse the bioactive compounds of the leaves of Conocarpus lancifolius (C. lancifolius). The GC-MS analysis of the hot methanolic extract of the leaves (HMEL) of C. lancifolius exhibited the bioactive compounds such as 1-(3-Methoxy-2-nitrobenzyl) iso quinoline, morphin-4-ol-6,7-dione, 1-bromo-N-methyl-, phytol, hexadecanoic acid, 2,3-dihydroxypropyl ester, 2,2':4',2”-terthiophene, ethyl iso-allocholate, caryophyllene oxide, campesterol, epiglobulol, cholestan-3-ol, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Hexadecanoic acid 2,3-dihydroxypropyl ester (known as palmitate) is a biologically active fatty acid with reported antitumor activity against human leukemia cells, with no side effects or cytotoxicity to normal human dermal fibroblast ( Al-Wahaibi et al, 2020 ). It was reported that the broad-spectrum antimicrobial activity of Conocarpus lancifolius leaf extract and its antitumor activity against breast cancer might be attributed to the presence of hexadecanoic acid, 2,3-dihydroxypropyl ester ( Moni et al, 2021 ). Furthermore, oleic acids are biologically active monounsaturated fatty acids with reported antibacterial, antioxidant, and antiviral activities ( Dilika et al, 2000 ; Wei et al, 2016 ; Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hexadecanoic acid 2,3-dihydroxypropyl ester (known as palmitate) is a biologically active fatty acid with reported antitumor activity against human leukemia cells, with no side effects or cytotoxicity to normal human dermal fibroblast ( Al-Wahaibi et al, 2020 ). It was reported that the broad-spectrum antimicrobial activity of Conocarpus lancifolius leaf extract and its antitumor activity against breast cancer might be attributed to the presence of hexadecanoic acid, 2,3-dihydroxypropyl ester ( Moni et al, 2021 ). Furthermore, oleic acids are biologically active monounsaturated fatty acids with reported antibacterial, antioxidant, and antiviral activities ( Dilika et al, 2000 ; Wei et al, 2016 ; Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these have been reported as potent bioactive components. The spectrum of antibacterial activity was ascribed by several authors to the presence of hexadecanoic acid, 2,3-dihydroxypropyl ester [ 34 ] and 1,2-benzenedicarboxylic acid, bis(2-ethylhexyl) ester [ 35 ]. The other components include octadecanoic acid, 2,3-dihydroxypropyl ester (Stearin), a glycerol derivative, which has anticancer and antimicrobial activities [ 36 ], and 9,12-Octadecadienoic acid (Z,Z)-, which is a fatty acid reported to have anti-inflammatory, cancer-preventive, and antiprostatitic properties [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that distinct extracts of multiple medicinal plants obtained from various locations around the Kingdom of Saudi Arabia and belonging to different Botanic families exhibit interesting antibacterial and antifungal properties. Among them species from Boraginaceae, Asteraceae, Polygonaceae, Rhamnaceae, Resedaceae, Euphorbiaceae Combretaceae and Acanthaceae (Moni et al, 2023;Aly and Bafeel, 2010;Alamri and Moustafa, 2012;Shahat et al, 2017;Okla et al, 2021).…”
Section: Determination Of Minimal Inhibitory Concentrations (Mic) By ...mentioning
confidence: 99%